Atypical teratoid/rhabdoid tumour with CDK6 amplification in a child: a case report and literature review - Li, Zhibin; Wang, Yubo; Liu, Yuanhao; Jiang, Yining; Han, Xuefei; Zhao, Liyan; Li, Yunqian (Frontiers in Pediatrics, 2023)
Atypical teratoid/rhabdoid tumours (AT/RTs) are rare central nervous system neoplasms that frequently occur in infants and children and have a very poor prognosis. In recent years, molecular analysis of AT/RTs has shown that biallelic inactivation of SMARCB1 (INI1, SNF5, BAF47) or SMARCA4 (BRG1) frequently occurs. Here, we present a case of basal ganglia AT/RT with SMARCB1 gene deficiency and CDK6 gene amplification in a 5-year-old child. A 5-year-old boy was hospitalized due to a one-week history of frontal and parietal headache. Magnetic resonance imaging (MRI) demonstrated a 3×2×1.5 cm heterogeneous enhanced mass located at the right basal ganglia that partially protruded into the right lateral ventricle. The lesion was successfully resected under electrophysiological monitoring and neuronavigation. The postoperative pathological examination implied an AT/RT diagnosis, with loss of SMARCB1 protein, SMARCB1 gene deficiency and CDK6 gene amplification. Unfortunately, the patient died due to respiratory and circulatory failure at 5 weeks after the operation. To date, standard regimens have not yet been established due to the lack of large-scale prospective studies for AT/RT. The p16-RB signalling pathway should be considered as a potential target gene for AT/RT treatment modalities. Apart from traditional regimens, targeted therapies, especially CDK4/6 inhibitors, are likely a promising therapeutic option for AT/RT treatment.